2020
DOI: 10.1111/pai.13185
|View full text |Cite
|
Sign up to set email alerts
|

The inflammatory potential of diet impacts the association between air pollution and childhood asthma

Abstract: Background: Inhalation of fine particulate matter (PM) can cause systematic inflammation and oxidative stress, which may further aggravate the development and progression of asthma. Although nutritional intake of fatty acids and antioxidants may attenuate some effects of fine PM, the role of the inflammatory potential of diet has not been addressed. Therefore, we aimed to investigate possible modulatory effects of dietary inflammatory potential on the association between indoor air pollution and childhood asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…In addition, they found specifically a positive correlation for this protective effect of vegetables in children presenting a lower genetic risk score. De Castro Mendes et al and others have shown earlier that the diet may influence inflammatory parameters and impact asthma in association with the environment 10,11 . The current study expends the effect of the diet on rhinitis.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…In addition, they found specifically a positive correlation for this protective effect of vegetables in children presenting a lower genetic risk score. De Castro Mendes et al and others have shown earlier that the diet may influence inflammatory parameters and impact asthma in association with the environment 10,11 . The current study expends the effect of the diet on rhinitis.…”
supporting
confidence: 55%
“…De Castro Mendes et al and others have shown earlier that the diet may influence inflammatory parameters and impact asthma in association with the environment. 10,11 The current study expends the effect of the diet on rhinitis.…”
mentioning
confidence: 99%
“…As obesity is now a well-known risk factor for asthma, trying to understand better how obesity might modify associations between oxidant exposures, such as air pollution, and asthma is particularly relevant [147]. Some studies have suggested that diet may act as an effect modifier and modulate the adverse effect of air pollution on asthma outcomes [148][149][150]. Investigating the potential interaction between exercise and air pollution, with the issue of whether or not increased exposure to air pollution during exercise outweighs the beneficial effects of physical activity on asthma is also critical in order to guide public health interventions [144,151].…”
Section: The Association Between Nutritional Factors and Asthma: An Ementioning
confidence: 99%
“…Two studies investigated the role of the diet inflammatory index on allergy development in the children (116,117) and neither one of these could find an association between diet inflammatory scores and asthma in the child. One study found that indoor pollution on asthma outcomes was more severe in those with a pro-inflammatory diet than those following an anti-inflammatory diet (116).…”
Section: The Diet Inflammatory Indexmentioning
confidence: 99%
“…The role of diet indices in infancy vs. subsequent development of allergic outcomes in later childhood have not been conducted. A number of studies have however looked at the Mediterranean diet in childhood vs. allergy outcomes, using either the KIDMED mediterranean score ( 99 , 101 106 ) or the adult EPIC score ( 107 115 ) and the diet inflammatory index ( 116 , 117 ) ( Table 5 ).…”
Section: Diet Indices In Childhoodmentioning
confidence: 99%